Influencia De Los Parámetros De Síntesis En Las Propiedades Morfológicas De Nanopartículas De Plata Y Su Correlación Con La Resonancia Superficial Del Plasmón (2024)
Silver nanoparticles (AgNPs) are synthesized by two methods. In the first method, a mixture of NaBH4 (reductant) and sodium citrate (dispersant) is added dropwise in 0.93 mM AgNO3 solution (precursor), while, in the second method, the reductant was added dropwise to the precursor-dispersant mixture. In this regard, the effect of pH on the synthesis was investigated, different media were used: water (control), citrate buffer pH 4.0, 20 mM, phosphate buffer pH 7.0, 20 mM and ammonium buffer pH 10.0, 20 mM. Finding at pH 10.0 a shift of approximately 20 nm in the surface plasmon resonance compared to the control, in parallel at pH 4.0 and 7.0 no shift was observed. Using the control medium, the effect of pressure at 1.7 MPa and temperature of 200°C was evaluated for 4, 8 and 27 hours. A shift of approximately 20 nm was observed at all time conditions studied. The findings obtained in this study suggest that both pH alkalinity and the application of elevated pressure exert a significant impact on the morphology of silver nanoparticles (AgNPs).